HUBUNGAN ANTARA INTERLEUKIN- 6 DAN C-REACTIVE PROTEIN PADA SIROSIS HATI DENGAN PERDARAHAN SALURAN MAKANAN BAGIAN ATAS - Mariadi, I Ketut; Wibawa, I Dewa Nyoman (journal of internal medicine, 2012)
Variceal bleeding is a frequent complication of liver cirrhosis. Upper gastrointestinal (GI) bleeding is a risk factor for infection. The severity of liver cirrhosis was correlated with infection and GI bleeding. Bacterial infection and endotoxin promote cytokine proinflammation (IL-6) release from monocyte. IL-6 stimulates the liver to produce CRP. Does liver cirrhosis affect the CRP production? Recently, there are no data about the correlation of IL-6 and CRP in liver cirrhosis with upper gastrointestinal bleeding. A cross-sectional analytic study was performed to describe the correlation between IL-6 and CRP in liver cirrhosis patient with upper gastrointestinal bleeding. We performed a cross-sectional analytic study in 52 liver cirrhosis patients. The liver cirrhosis patients with upper gastrointestinal bleeding in last 14 days, absence of steroid and statin treatment, without hepatoma, and GFR 15 ml/mnt/1.73 m2, were collected consecutively. The correlation of IL-6 and CRP was analyzed with Pearson correlation test, mean difference of CRP between Child Turcotte Pugh (CTP) group was analyzed by Ancova test continued with post hoc Tamhane test, the effect of CTP on CRP production was analyzed with Ancova test. Seventy-five percent out of 52 samples were male and the rest were female. Two of them (3.8%) with CTP score A, 20 (38.5%) CTP score B and 30 (57.7%) CTP score C. Mean of IL-6 was 28.29 ± 34.60. Mean of CRP was 17.17 ± 28.80 mg/L. We found strong positive correlation between IL-6 and CRP (r = 0.610; p<0.001). CTP score didnt have significant independent effect on correlation of IL-6 and CRP level (F=2.33; p=0.108). Significant mean difference of CRP was found between CTP score group (F=4.27; p=0.02). In conclusion, Interleukin-6 has a strong correlation with CRP in liver cirrhosis with upper GI bleeding. CRP level is significantly higher in severe liver cirrhosis. And the degree of liver damage doesnt have significant independent effect on correlation of IL-6 and CRP level. These results show us that hepatocyte in liver cirrhosis still adequately produce CRP.
Keywords: IL-6, CRP, liver cirrhosis, CTP score PENDAHULUAN